A new microcrinoid (Roveacrinidae) from the Aptian–Albian of the Sergipe-Alagoas Basin, northeastern Brazil. (May 2023) - Pierezan, Bruna Poatskievick; Gale, Andrew S.; Fauth, Gerson
Abstract: A new genus and species of roveacrinid, Sergipecrinus reticulatus, is described from the upper Aptian and lower Albian of the Sergipe-Alagoas Basin, northeast Brazil, on the basis of abundant cups and isolated brachials from core SER-03. This is the first roveacrinid of Aptian age to be described and provides important information concerning the early history of the Roveacrinidae.